Insulin Resistance and Metabolic Syndrome Increase the Risk of Relapse For Fertility Preserving Treatment in Atypical Endometrial Hyperplasia and Early Endometrial Cancer Patients - Li, Xingchen; Fan, Yuan; Wang, Jiaqi; Zhou, Rong; Tian, Li; Wang, Yiqin; Wang, Jianliu (Frontiers in Oncology, 2021)
Objective: Fertility-sparing treatment for young women with atypical endometrial hyperplasia (AEH) and early endometrial cancer (EC) is a difficult challenge. Insulin resistance (IR) and metabolic syndrome (MetS) are two potentially crucial, but currently enigmatic, factors in the recurrence of AEH and early EC patients. In this study we attempt to elucidate these factors. Methods: A retrospective study was conducted from January 2010 to December 2018. Risk factors for recurrence and complete remission time after recurrence (RCR time) were investigated. ROC curves were built to estimate the accuracy of the metabolic characteristics and Kaplan-Meier (K-M) analysis was used to calculate recurrence-free survival (RFS) for patients with various IR or MetS statuses. Results: A total of 111 AEH or early EC patients met the criteria and were enrolled in our study. Univariate analysis found that BMI ≥25kg/m2 (OR=2.7, 95% CI: 1.1-6.4, P=0.03), IR (OR=9.5, 95% CI: 3.3-27.0, P<0.001), MetS (OR=4.9, 95% CI:1.5-15.5, P=0.008), IR+ and MetS+ (OR=21.0, 95% CI: 4.8-92.7, P<0.001), histological type (OR=3.5, 95% CI: 1.5-7.9, P=0.003), and maintenance treatment (OR=0.3, 95% CI: 0.1-0.6, P=0.005) were all significantly associated with recurrence and longer RCR time. Among these factors, IR and MetS were determined to be two independent risk factors for recurrence. Moreover, using IR and MetS as markers significantly improved the diagnostic accuracy of recurrence for fertility-sparing treatment patients (AUC=0.818, P<0.05) and may play synergistic roles in suppressing treatment. K-M analysis indicated both metabolic features played important roles in RFS (P<0.05). Conclusion: Both IR and MetS were significantly associated with recurrence and longer RCR time in AEH and early EC patients receiving fertility-sparing treatment.